Financial Contagion Through Bank Deleveraging : Stylized Facts and Simulations Applied to the Financial Crisis - Tressel, Thierry (IMF Working Papers; Working Paper ;, 2010)
The financial crisis has highlighted the importance of various channels of financial contagion across countries. This paper first presents stylized facts of international banking activities during the crisis. It then describes a simple model of financial contagion based on bank balance sheet identities and behavioral assumptions of deleveraging. Cascade effects can be triggered by bank losses or contractions of interbank lending activities. As a result of shocks on assets or on liabilities of banks, a global deleveraging of international banking activities can occur. Simple simulations are presented to illustrate the use of the model and the relative importance of contagion channels, relying on bank losses of advanced countries' banking systems during the financial crisis to calibrate the shock. The outcome of the simulations is compared with the deleveraging observed during the crisis suggesting that leverage is a major determinant of financial contagion.